Evaluating the Effectiveness of the Merdeka Belajar Kampus Merdeka (MBKM) Program in Enhancing Students' Job Readiness: A Study at the Faculty of Education, State University of Jakarta - Rahmatiah, Rahmatiah (International Journal of Business, Law, and Education, 2025)
This study aims to examine the effectiveness of the Merdeka Belajar Kampus Merdeka (MBKM) program in enhancing the job readiness of graduates from the Faculty of Education, State University of Jakarta (FIP UNJ). Employing a quantitative research approach, the study utilized a survey method with data collected through a structured questionnaire distributed via Google Forms. The instrument, developed using a Likert scale, was administered to a sample of 323 FIP UNJ students selected through proportional random sampling to ensure representativeness based on the population's structure. The findings indicate that students perceive the MBKM program positively. It is seen as instrumental in strengthening experiential learning, enhancing both hard and soft skills, and preparing them for the professional world. The program has significantly contributed to aligning higher education outcomes with labor market demands, thereby improving the overall quality of graduates. Furthermore, MBKM has played a vital role in nurturing students' intellectual and personal development. Despite its benefits, the program faces challenges in implementation, particularly in terms of limited socialization and insufficient collaboration with industry partners. These barriers can be addressed through enhanced outreach, stronger institutional partnerships, ongoing monitoring and evaluation, and improved resource allocation to support effective program delivery.